EVALUASI PELAKSANAAN PENATAAN RUANG TERBUKA HIJAU PUBLIK (TAMAN PUBLIK) DI KECAMATAN SEMARANG TIMUR BERDASARKAN PERDA KOTA SEMARANG NO 7 TAHUN 2010 TENTANG PENATAAN RUANG TERBUKA HIJAU - Dewi, Kidung Sukma; Lituhayu, Dyah (Journal of Public Policy and Management Review, 2016)
Open Green Space is an important component needed by citizen to do outdoor daily activity. A district has ideally 20% Public Open Green Space of total area. Semarang Timur District has not accomplished 20% public open green space yet because the area tends to flooding that causes the green plants not to grow well. Open Green Space arranging implementation in the Semarang Timur District refers to Local Regulation of Semarang No. 7 of 2010 about Open Green Space Arrangement. Research method uses descriptively qualitative approach with observation, interview, and literary review as the data collecting technique. The interviewees are Landscape Gardening Division Head of Hygiene and Landscaping Gardening Department of Semarang, Developing Section Chief of Eastern Semarang District, and people of the district. The research results that Open Green Space arranging implementation in the Semarang Timur District is not fully accomplished, proven by lack of Public Open Green Space especially Public Park that is supposed to be 8.95 ha, the work has just accomplished 1.7 ha. However, the people have felt the park Public Park Open Green Space benefit as the place to get along for adults and to play around for children. The research states that people participation in the Public Park Open Green Space care is still not enough, proven that Rejomulyo Park in the Semarang Timur District is lack of handling. Recommendation to properly implement for Public Park Open Green Space arrangement in the Eastern Semarang District is to issue a regulation that requires every sub-district to develop Public Park.